Studying steppe cherry cultivars in Chelyabinsk Province - A. A. Vasiliev; F. M. Gasymov; V. R. Galimov (Труды по прикладной ботанике, генетике и селекции)
The aim of the research was to study steppe cherry cultivars of various environmental origin in the context of their productivity, environmental plasticity and stability in the environments of Chelyabinsk Province. Evaluation of the studied set of cultivars helped to identify adaptable steppe cherries: ‘Izobilnaya’ (4.39 t/ha; KA = 1.54), ‘Shchedraya’ (4.42 t/ha; KA = 1.37), ‘Galimovka’ (3.83 t/ha; KA = 1,36), ‘Mayak’ (4.04 t/ha; KA = 1.30), ‘Ashinskaya’’ (t/ha 3.42; KA = 1.28) and ‘Mechta Zauralya’ (3.29 t/ha; KA = 1.07). The most interesting among them are intensive-type cultivars responding well to improved growing conditions, such as the steppe cherry cultivars developed at Sverdlovsk Horticultural Breeding Station: ‘Shchedraya’ (bi = 1.99), ‘Mechta Zauralya’ (1.85) and ‘Mayak’ (1.47). The Chelyabinsk cultivar ‘Galimovka’, submitted for state trials in 2018, falls under the category of environmentally plastic and stable cultivars (bi = 0.77; Si2 = 0.5), while cv. ‘Ashinskaya’ demonstrated during the tests a neutral genotype, as it poorly responded to changing environmental conditions (bi = 0.32; Si2 = 0.1). A new cultivar, ‘Vita’, with a fairly high yield (3.05 t/ha), developed at Sverdlovsk Horticultural Breeding Station, belongs to the environmentally plastic category (bi = 1.10), but its yield stability proved to be insufficient in the environments of the Southern Urals (Si2 = 2.2).